Konsep Perancangan Wisata Kuliner Tempat Pelelangan Ikan Lappa Lelong Sinjai Dengan Penerapan Arsitektur Perilaku - Sulfaida, Sulfaida; Nursyam, Nursyam; Nuryuningsih, Nuryuningsih (The Department of Architecture, Faculty of Science and Technology, Alauddin Islamic University of Makassar, 2023)
Abstract_As a maritime country, Indonesia has vast territorial waters, which have a significant potential for fish resources—culinary tourism to taste the results of natural resources in the ocean. The problem formulation is based on how to design a Lappa Lelong culinary tour to get a qualified design to become a reference for a situation in fish trading places. The data collection method uses three systems, namely: secondary data, where a literature review is carried out; primary data, namely data generated directly or field observations as well as precedent studies, which carry out comparative studies on the design of buildings where fish auctions are held and concepts related to architectural behavior. Geographically, Sinjai Regency is located at 5°2''56